Dakwah dalam Narasi Berita: Studi Representasi Nilai Keislaman dalam Pemberitaan Harian Suara Muhammadiyah - Nina Nina; Muhammad Khoerul Hadist; Naufal Ramadian; Triyanto Triyanto (Ulul Albab: Majalah Universitas Muhammadiyah Mataram, 2026)
This study aims to analyze the representation of progressive Islamic values and the framing strategies used to shape public perception. The study employs a qualitative approach with a descriptive-interpretive design, grounded in Critical Discourse Analysis and framing theory. The data sources consist of news articles from the Suara Muhammadiyah daily newspaper, collected through documentation and text analysis. The results show that news coverage frames the Ramadan fast as a means of character building, self-control, and social contribution that brings peace to the wider community, including non-Muslims. Moral and social framing reinforces noble ethical values and solidarity, while metaphors are used to reinforce ideological perceptions. The existence of Islamic media serves as a mediator in the construction of ideology and the practice of dakwah bi al-qalam (proselytizing through the pen), and the study recommends the development of more inclusive and contextual narrative strategies.